Prices and Currency in Japan - Clark, Victor S. (Quarterly Journal of Economics, 1920)
Rise of prices and wages, 433. — Synchronism with changes in the United States, 434. — Currency inflation and prices keep step, 434. — Government borrowing no cause of currency expansion, 435. — Bank notes expanded but deemed secure, 437. — Rise of interest rate, 439. — Rising market expected to continue, 441. — Criticisms and forebodings, 442.